First-time electrical characterization of nanotubular ZrO2 films for micro-solid oxide fuel cell applications. Issue 18 (14th May 2015) - Buyukaksoy, Aligul; Fürstenhaupt, Tobias; Birss, Viola I.
<x xml:space="preserve">Abstract</x> In this work, anodically grown ZrO2 nanotubes (NTs) are examined for the first time for use in micro solid oxide fuel cell (μ-SOFC) applications.